SUSTAINABLE HOUSING AFFORDABILITY IN SABAH - Said, Rosli; Ab. Majid, Rohayu; Alias, Anuar; Mohd Adnan, Yasmin; Razali, Muhammad Najib (PLANNING MALAYSIA, 2016)
Sabah is one of the states in Malaysia has shown remarkable growth in housing industry where its housing sector has thrived owing to growing market and active supply and demand dynamics. However, the rapid increase in housing price has created greater concern among the researchers about the sustainability of the housing sector in this country. The aspect of sustainability has seem been neglected by the industry players. Consequently, it will give impact to the environment which contrasts with the aim of the built environment to create sustainable development. This is because affordable housing is always being associated with cheap and low-quality houses. This research is aim to assess the best area in the state of Sabah to build sustainable affordable housing scheme. The results indicate that area with high utility degree is the best area that conforms to the sustainable housing affordability factors. Likewise, an area with a lower ranking in utility degree can be described as a worst-performing area. The originality of this research has contributed to a real picture of sustainable housing affordability in Malaysia, particularly the state of Sabah.